Recife, Pernambuco, Northeast Brazil: comparison between cases of dengue, chikungunya and zikavirus in the year 2021, using the Python language - Félix de Castro, Angélica; Gondim de Oliveira , Amanda; Felipe Fernandes Vieira, George (Seven Editora, 2023)
Arboviruses are diseases caused by so-called arboviruses, which include dengue virus, zika virus, chikungunya fever and yellow fever. They are a public health problem in the world mainly due to their potential for dispersion, their ability to adapt to new environments and hosts, the possibility of causing extensive epidemics and their universal susceptibility. The present work consists of a study of cases of arboviruses in Recife, capital of the state of Pernambuco, Northeastern Brazil, in the year 2021. First, data were extracted from official sources of the Municipality of the city of Recife on cases of dengue, chikungunya and zika virus in the year 2021. After this extraction, Python commands were applied to understand how the outbreak of these specific diseases occurred in Recife and to generate heat maps of the neighborhoods most affected by arboviruses. It was possible to conclude that arboviruses are not worrying reasons for death and do not cause high hospitalization of patients. As for the heat maps, the neighborhoods of Varzea, Ibura, Iputinga, Imbiribeira, Vasco da Gama and Dois Unidos were the most affected by the presence of the three diseases. In comparative terms, dengue and chikungunya have similar symptoms (fever and headache). DOI: https://doi.org/10.56238/devopinterscie-149